2015
DOI: 10.7243/2050-1323-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of key plant nutrients (N & P) in hokersar, a typical wetland of Kashmir Himalaya, India

Abstract: Hokersar wetland suffers highly due by nutrient inputs from the catchment area, internal wetland processes and various types of anthropogenic pressures around. To characterize nutrient dynamics of the wetland, nitrogen (N) and phosphorus (P) samples were collected from six study sites in the Queen wetland of Kashmir Himalaya for a period of one year from Sep. 2012 to Aug. 2013. Clear spatial and temporal variations were observed among the recorded parameters (ammonical nitrogen, nitrate nitrogen, total orthoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
2
7
1
Order By: Relevance
“…Water is a requisite medium between varied factors that plays a decisive role in wetland ecology and the quality and management of water is a fundamental part for wetland conservation. Further, the importance of water for aquatic life as the fulcrum of biochemical metabolism rests on its physical and chemical properties (Shah et al 2015; Bhateria and Jain 2016; Falah and Haghizadeh 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water is a requisite medium between varied factors that plays a decisive role in wetland ecology and the quality and management of water is a fundamental part for wetland conservation. Further, the importance of water for aquatic life as the fulcrum of biochemical metabolism rests on its physical and chemical properties (Shah et al 2015; Bhateria and Jain 2016; Falah and Haghizadeh 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The wetland is fed by two inlet streams, Doodhganga from east and Sukhnag Nalla from west. The excess water is drained out through an outlet gate known as Needle-Gate on the north-west of the wetland near the village Sozieth, having a weir and lock system, which regulates the water level to provide a better habitat for migratory waterfowl during winter (Shah et al 2015) (Fig. 1).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption isotherm data were analyzed in terms of Langmuir and Freundlich isotherms (figure 5). Langmuir and Freundlich isotherms are the most widely used models for solid-liquid adsorption [4][5][6]. Based on the values of the correlation coefficients, it can be inferred that the equilibrium adsorption data were better described by the Langmuir adsorption model.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they cannot be used to reduce concentrations of these ions to permissible levels. Nowadays sorption method is generally given preference over other water purification techniques due to its high efficiency, easy handling; besides, it is environmentally friendly [1][2][3][4][5][6][7][8][9][10][11][12]. Literature review [1][2][3][4][5][6][7] showed that mineral sorbents are cheap and available material capable to remove heavy metal ions from industrial wastewater.…”
Section: Introductionmentioning
confidence: 99%